(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
There is a lot of data on the internet. The data is increasing exponentially and even the data on the internet is in unstructured format. The semi-structured and unstructured data make it difficult to extract relevant data from the Web. Even if the data is extracted properly the efficiency is quite low which make the data irrelevant. To answer this problem there comes in picture the Web Scraping. Web scraping can be defined as the extraction of data from the website, in general term. The project with the help of web scraping will make the data extraction from the website easily. This approach will allow scraping the data from various website, which will reduce the human effort, save the time, also increase the data relevancy efficiency. This will help the user to extract data from the website and save the data for his purpose and use as the user wants it. The scraped data can be used to create database or for analysis purpose as well as for various other purpose.